(untitled) (Педагогіка вищої та середньої школи, 2022)
In the article of Korotkova Yuliya “The structure of the plans of the pedagogical departments for the preparation of primary school teachers in Greece” the structure of curriculums, types of disciplines of 9 pedagogical university departments for the preparation of primary-school teachers are discussed.